Group G Streptococci in association with brain abscess: a rare occurrence - Parimala Subramani; Vidhya Raja; Bipinchandra Bhagath Lingaiah; Beena Prasavangada Madappa; Hariprakash Chakravarthy (Journal of Infection in Developing Countries)
Brain abscess is a serious life-threatening infection of the brain parenchyma. We are reporting a rare case of brain abscess caused by Group G Streptococcus in a 12 year-old female child who presented with neurological symptoms. She was diagnosed with congenital anomalies of the heart at birth. She was treated with amoxyclav and ciprofloxacin. The child recovered and was discharged uneventfully.